Pressions Anthropiques Et Dynamique D’occupation Des Terres Dans Le Terroir De Ziguéna, Zone Cotonnière Du Mali - Ballo, Abdou; Traoré, Souleymane Sidi; Coulibaly, Baba; Diakité, Cheick Hamalla; Diawara, Moriké; Traoré, Alou; Dembélé, Sidi (European Scientific Journal, ESJ, 2016)
In Ziguéna terroir, the combined effects of drought and anthropogenic actions led to the widespread degradation of vegetation cover and of land. This work aimed at characterizing the dynamics of land use and land cover in relation to anthropogenic pressures in Ziguéna terroir. The methodology consisted in identifying and characterizing land use and land cover classes. Landsat images for the years 1986 and 2013 and population data for the years 1987, 1998 and 2009 were used. Visual interpretation of the images and post-classification comparison of the results were used to generate land use and land cover classes and calculate their rate of change. The results reveal that the natural vegetation has lost 55% of its original coverage (1514.3 ha) between 1987 and 2013. During the same period, the agricultural area increased by 47% (1608 ha). The projection of land use and land cover classes predicted an increase of agricultural land of about 34.60% by year 2030 compared to its coverage of year 2013 (+1191.03 ha) at the expense of natural vegetation which will lose about 40.63% of its coverage (-1121.70 ha). The dynamics of agricultural land is strongly linked to population growth rates with a correlation coefficient r equal to 0.99. This confirms a strong anthropogenic influence on land use and land cover dynamics. The results show the usefulness of remote sensing for mapping land use and land cover. Nevertheless it would be interesting to take into account the socioeconomic aspects for proper understanding of the dynamics.